Diagnostics of technical condition of high-voltage equipment of traction rolling stock (Transport systems and technologies, 2019)
A large amount of scientific research in the field of diagnostics of high-voltage electrical equipment installed on various types of power substations, has significantly improved the reliability and trouble-free operation of it. Particular attention is now being paid to the development of methods that ensure state monitoring under operating voltage. In contrast to the dynamic integrated fault diagnosis method, based on the Bayesian network, there is continuous, and more often automatic control, provided by analyzing dissolved gases, recording the physicochemical characteristics of insulation, measuring partial discharges, electrical parameters, and the like.Diagnostic reliability is significantly improved by using several independent parameters of deterministic value. Their list also includes a diagnostic method based on an analysis of the spectra of the equipment’s own electromagnetic radiation.This work presents the results of testing the use of a diagnostic technique for high-voltage equipment of electric rolling stock by the spectrum of its own electromagnetic radiation under load, with a demonstration of the correlation between the defect and fluctuations in the radiation spectrum.It is shown that noise can be caused both by the processes of electric current flow and by chaotic changes in other non-electrical parameters of the equipment, which will turn into changes in the values of currents and voltages. A diagnostic technique based on a noise emitting model allows one to evaluate the state of external and internal structural elements, thereby substantially deepening and increasing the reliability of diagnostics.The purpose of the research is to determine the possibility of using the analysis of the spectra of the own electromagnetic radiation of high-voltage equipment of traction electric rolling stock to diagnose its technical condition during operation under load.On the other hand, when monitoring electromagnetism of frequency, monitored by the first estimates of natural fluctuations of electromagnetism in frequency smugs, the value of the error is incorrect.Measurements of the magnitude of electromagnetic radiation in the frequency bands when monitoring the technical condition of high-voltage equipment must be carried out quite often, so the monitoring system should be either stationary or portable measuring instruments should be available to the duty personnel serving the controlled units and have minimal training in performing measurement operations.In the case of traction electric rolling stock, it is advisable to consider the development and implementation of stationary stands for the diagnosis of high-voltage equipment, which uses the method of analysis of its own electromagnetic radiation.
Keywords: traction electric rolling stock, diagnostics, high-voltage equipment, main controller, electromagnetic radiation, energy spectrum, defectiveness measure